In Vitro Characterization of Aerosolized Albuterol Generated by a Jet Nebulizer and Delivered through a Heated Flow Nasal Cannula System - Ariel Berlinski; Joshua Spiva (MDPI AG, 2022)
Pediatric patients receiving respiratory support with heated flow nasal cannula (HFNC) systems frequently receive inhaled medications. Most available data have been obtained with vibrating mesh nebulizers that are expensive. Data are lacking regarding the feasibility of using less expensive devices such as continuous output jet nebulizers. The characteristics of the aerosols generated by jet nebulizers operated at different conditions (6 and 9 L/min) were studied alone and connected to a HFNC system and different size cannulas using a cascade impactor and spectrophotometry (276 nm). Aerosol characteristics changed while traveling through the HFNC system. Initial size selection occurred at the exit of the circuit (before connecting to the cannula) with all aerosol <5 µm. Nasal cannula size further selected aerosols and reduced drug delivery. The operating flow of the nebulizer did not affect the delivered mass but higher flows generated smaller particle size aerosols. The addition of supplemental flow significantly reduced the delivered mass. The measured aerosol characteristics would likely result in intrapulmonary deposition. The delivery of aerosolized albuterol generated by a continuous output nebulizer placed in the inlet of a HFNC system and connected to large or XXL cannulas is feasible.